THE RELEVANCE OF WHAT SEEMS IRRELEVANT: REMARKS ON THE RELATIONSHIP BETWEEN PHATIC UTTERANCES AND SOCIOPRAGMATIC FAILURE - Padilla Cruz, Manuel (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Sociopragmatic failure can be explained from a cognitive viewpoint in terms of differences in the specific knowledge internalized by interlocutors about the expected behavior in a particular situation. The aim of this paper is to show that this specific knowledge is essential for a correct understanding of conversations in which apparently no relevant information is transmitted. Each social or cultural group establishes procedures for carrying out different speech acts or for creating or modifying relationships among its members. Phatic utterances must therefore be understood as indispensable elements within the sociocultural conventions according to which a group operates. They transmit relevant information in such a way that the speaker who uses them follows a set of internalized assumptions that indicate to her the behavior considered correct in a particular situation. This has clear implications for the L2 class, where students can accumulate information about the correct behavior in certain contexts and avoid sociopragmatic failures.